Frequency of Left Ventricular Systolic Dysfunction in Patients with Wellens Syndrome Undergoing Angiography - Anees, Neelam; Akhtar, Parveen; Elahi, Noor; Fareed, Sumera; Shaheer, Muhammad; Zafar, Osama; Yaqoob, Nasir (Indus Journal of Bioscience Research, 2025)
Background: Wellens syndrome is an electrocardiographic marker of critical proximal left anterior descending (LAD) artery stenosis and a strong predictor of anterior wall myocardial infarction if left untreated. Objective: To determine the frequency of left ventricular systolic dysfunction in patients with Wellens syndrome undergoing coronary angiography. Methods: This descriptive cross-sectional study was conducted at the in-patient department of the National Institute of Cardiovascular Diseases (NICVD), Karachi, Pakistan, from March 2025 to 10 June 2025. A total of 187 patients were included using non-probability consecutive sampling. Patients aged 18–60 years of both genders undergoing coronary catheterization were enrolled, excluding those with previously established LVSD. Results: The mean age of the study population was 51.3 ± 7.8 years, with 110 (58.8%) males and 77 (41.2%) females. Diabetes mellitus was present in 92 (49.2%) patients, hypertension in 101 (54.0%), and smoking history in 77 (41.2%). Angiography revealed proximal LAD lesions in 164 (87.7%) patients. LVSD was observed in 111 patients, giving a frequency of 59.4%. Among these, mild LVSD was present in 48 (25.7%), moderate in 39 (20.9%), and severe in 24 (12.8%). LVSD was significantly more frequent in patients with diabetes (68.5% vs. 50.0%, p = 0.01), hypertension (65.3% vs. 52.3%, p = 0.04), and triple-vessel disease (77.8%, p < 0.001). Conclusion: A high frequency of left ventricular systolic dysfunction was observed in patients with Wellens syndrome undergoing angiography, particularly in those with diabetes, hypertension, and multivessel disease.